1983
DOI: 10.1002/abio.370030405
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomes of alkane‐utilizing yeasts metabolic functions and practical aspects

Abstract: One of the most striking features of alkane-grown yeast cells is conspicuous appearance of peroxisomes in harmony with a high level of ciltalase. This unique phenomenon was first demonstrated in the authors' laboratory, and the metabolic functions of peroxisomes in yeasts utilizing alkmes has been established with intact peroxisomes isolated by density gradient centrifugation. The organelles participate in the degradation of fatty acids derived from alkanes to C,-units and the synthesis of gluconeogenic interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1985
1985
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…81 bon utilisation rather than an adaptation for uptake. Such structures are exemplified by microbodies in alkane-grown yeasts which are structures rich in oxidative enzymes (Fukui & Tanaka 1979). Indeed, Hommel & Ratledge (1990) showed that the fatty alcohol oxidases involved in n-alkane metabolism by Candida bombicola were solely present in the microsomal fraction.…”
Section: Microbial Adaptations For Hydrocarbon Uptakementioning
confidence: 99%
“…81 bon utilisation rather than an adaptation for uptake. Such structures are exemplified by microbodies in alkane-grown yeasts which are structures rich in oxidative enzymes (Fukui & Tanaka 1979). Indeed, Hommel & Ratledge (1990) showed that the fatty alcohol oxidases involved in n-alkane metabolism by Candida bombicola were solely present in the microsomal fraction.…”
Section: Microbial Adaptations For Hydrocarbon Uptakementioning
confidence: 99%
“…Previous studies have demonstrated that as in microorganisms that can use uric acid as a carbon source (Vogels and Van der Drift, 1976), urate oxidase was the key enzyme involved in urate metabolism in yeasts. In the latter organism this enzyme is present in peroxisomes which developed in small numbers during growth of various yeast species in media containing uric acid as a nitrogen source (Fukui and Tanaka, 1979;Veenhuis et al, 1983b;Veenhuis and Harder, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that control of AO expression in P. pastoris is substantially transcriptional (17). A second point of interest in methylotrophic yeasts is the mechanism by which enzymes such as AO and catalase are compartmentalized in peroxisomes (18). Peroxisomal packaging of AO does not appear to involve a processed amino-terminal signal sequence (17).…”
mentioning
confidence: 99%